2022
DOI: 10.3390/sym14071471
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Certain Subclasses of Analytic Functions Involving the Jackson q-Difference Operator

Abstract: We introduce two new subclasses of analytic functions in the open symmetric unit disc using a linear operator associated with the q-binomial theorem. In addition, we discuss inclusion relations and properties preserving integral operators for functions in these classes. This paper generalizes some known results, as well as provides some new ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Jackson in the early twentieth century. Numerous mathematical fields, including number theory, combinatorics, orthogonal polynomials, fundamental hyper-geometric functions, and other sciences, including physics and the theory of relativity, have used it successfully [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Jackson in the early twentieth century. Numerous mathematical fields, including number theory, combinatorics, orthogonal polynomials, fundamental hyper-geometric functions, and other sciences, including physics and the theory of relativity, have used it successfully [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the area of geometric function theory of complex analysis, the q-derivative operator D q was used in the year 1990 by Ismail et al [29] to study a class of q-starlike functions and by Srivastava in his book chapter [30], which was published in 1989, to investigate the univalence, starlikeness and convexity properties of the generalized qhypergeometric function r Φ s involving r numerator parameters and s denominator parameters r, s ∈ N 0 := N ∪ {0} . Some recent studies, in which the q-derivative operator D q was applied to various subclasses of of the function classes A(p) (p 1), can be found in, for example, [31][32][33][34].…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…Based on the same idea, many authors have extensively studied the q-calculus operators (q-differential and q-integral operators) in GFT. A recent study on these operators acting on analytic functions can be found in [12][13][14][15][16][17][18][19]. For 0 < q < 1, Jackson [9,10] defined the q-differential operator, D q , of a function, ξ, as the following:…”
Section: Introductionmentioning
confidence: 99%